Hypoxia Stimulates Synthesis of Neutrophil Gelatinase-Associated Lipocalin in Aortic Valve Disease - Swaminathan, Ganesh; Krishnamurthy, Varun K.; Sridhar, Swetha; Robson, Denise C.; Ning, Yao; Grande-Allen, K. Jane (Frontiers in Cardiovascular Medicine, 2019)
Objective: Aortic valve disease (AVD) is commonly found in the elderly. It is characterized by dysregulated extracellular matrix (ECM) remodeling followed by extensive microcalcification of the aortic valve (AV) and activation of valve interstitial cells (VICs). The mechanism behind these events in aged AVs are largely unknown. Studies have reported expression of hypoxia inducible factor-1 alpha (HIF1) in calcific nodules in AVD, therefore we investigated the effect of hypoxia on ECM remodeling in aged AVs. Approach and Results: Western blotting revealed elevated expression of HIF1 and the complex of matrix metalloprotease 9 (MMP9) and neutrophil gelatinase-associated lipocalin (NGAL) in aged porcine AVs cultured under hypoxic conditions. Consistently, immunofluorescence staining showed co-expression of MMP9 and NGAL in the fibrosa of these porcine hypoxic AVs. Gelatinase zymography demonstrated that the activity of MMP9-NGAL complex was significantly increased in AVs in 13% O2 compared to 20% O2. Importantly, the presence of ectopic elastic fibers in the fibrosa of hypoxic AVs, also detected in human diseased AVs, suggests altered elastin homeostasis due to hypoxia. Conclusion: This study demonstrates that hypoxia stimulates synthesis and activity of matrix remodeling enzymes by HuAVICs and promotes dysregulated elastin remodeling in aged AVs. Additionally, our results provide insights for future studies exploring the mechanisms behind hypoxia-mediated elastin homeostasis alterations and AVD progression.